Laparoscopic-assisted Duhamel procedure with ex-anal rectal transection for total colonic aganglionosis - Zhang, Xi; Cao, Guo-qing; Tang, Shao-tao; Chang, Xiao-pan; Li, Shuai; Yang, Li; Li, Kang; Zhou, Ying; Yang, De-hua (Journal of pediatric surgery, 2018)
Laparoscopic-assisted Duhamel procedure has a larger anastomosis and a reservoir which allows early recovery of defecation frequency, but concerns have been raised regarding the long operative time, high incidence of pouchitis and Hirschsprung associated enterocolitis (HAEC). The purpose of this study was to evaluate the postoperative complications and functional outcomes for patients with TCA undergoing modified laparoscopic-assisted Duhamel procedure (MLDP) with ex-abdominal partial colectomy and ex-anal rectal transection. From 2011 to 2014, 16 patients with TCA who underwent MLDP were reviewed at our institution. Main modified techniques were to mobilize partial bowel through abdominal stoma opening, mobilize remaining colon, and dissect the retro-rectal space using laparoscopy, pull out and transect rectum ex-anally using a linear stapling device for creation of a short rectal pouch of 35~45mm. Seven patients who underwent classical laparoscopic Duhamel procedure (CLDP) with a long rectal pouch of 50–60mm between 2009 and 2011 were used as control group. Data were collected including demographics, laparoscopic technique, operative time, stool frequency, complications and continence outcomes. The operative time in MLDP group was significantly shorter than control group (3.0h vs. 4.7h, p=0.02). The incidence of postoperative HAEC in MLDP group was lower than control group (12.5% versus 42.9%; p=0.03) within the second postoperative year. Two patients (28.6%) experienced episodes of pouchitis in CLDP group and none was found in MLDP group. There was no significant difference in overall functional outcome between two groups, but the performance of MLDP group was better in terms of diapers required than CLDP group (1.80±0.45 vs. 1.00±0.64; p=0.02). All patients after 4years of age had a normal defecation frequency in both groups. MLDP is a safe, simple, and reliable technique for TCA. It has fewer postoperative complications due to the short rectal pouch. However, longer follow-up and a larger sample size are necessary to prove the efficacy in the treatment of TCA. Level 3.